Implementasi Sistem Pembayaran Dengan Metode Rapid Application Development (RAD) Berbasis Website Pada Madrasah Tsanawiyah Nurul Hasanah - Habi Risnanda; Hendri Ardiansyah (CV. Multi Kreasi Media, 2025)
The advancement of technology and scientific knowledge has encouraged educational institutions to adopt information systems as a means to enhance operational effectiveness, particularly in financial administration. At Madrasah Tsanawiyah Nurul Hasanah, the school tuition payment system is still conducted manually, requiring parents or students to be physically present at the school. This method is considered inefficient as it can lead to long queues, lost payment receipts, and recording errors. In response to these issues, this research was conducted to design a web-based school payment system using the Rapid Application Development (RAD) method, incorporating features such as student data management, billing, online transactions, and automated financial reporting. Based on the implementation results, the developed system has a positive impact on improving the efficiency of financial administration processes, minimizing data entry errors, and enhancing transparency between the school and parents. Through digital access, parents can easily monitor payment statuses, while the school gains more structured control over its financial records. The application of the RAD-based system proves to be an effective solution in replacing conventional methods and supports the transition toward digital transformation in the school environment.